2019
DOI: 10.1039/c8nr08720b
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles induce minimal hepatotoxicity and immunogenicity

Abstract: The absence of any significant toxicity associated with EVs in vitro and in vivo support the prospective use of EVs for therapeutic applications and for drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 46 publications
8
122
0
Order By: Relevance
“…In addition, the use of exosomes would avoid various issues related to cell therapy such as the inability to sterilize the cells, short shelf-life, and limited quality control (QC) before release [41,44]. A couple of studies have also reported that exosomes from MSCs and HEK 293T did not cause toxicity in vivo or in vitro [44][45][46][47][48]. A recent study suggested that long-term repetitive injection of exosomes does not induce toxicity [45].…”
Section: Exosomes and Extracellular Vesiclesmentioning
confidence: 99%
“…In addition, the use of exosomes would avoid various issues related to cell therapy such as the inability to sterilize the cells, short shelf-life, and limited quality control (QC) before release [41,44]. A couple of studies have also reported that exosomes from MSCs and HEK 293T did not cause toxicity in vivo or in vitro [44][45][46][47][48]. A recent study suggested that long-term repetitive injection of exosomes does not induce toxicity [45].…”
Section: Exosomes and Extracellular Vesiclesmentioning
confidence: 99%
“…The most promising delivery system for CRISPR epi-editors with prolonged expression is AAV (adeno-associated virus) vectors with a packaging capacity of 5 kb [50]. In spite the size of the SpCas9-gRNA-effector (Streptococcus pyogenes Cas9) complex exceeds an average packaging limit, the effective in vivo delivery is achievable with smaller dCas9 variants, or a different, less immunogenic delivery systems, such as EVs (extracellular vesicles), carrying CRISPR epi-editor plasmids or viral vectors [50][51][52][53][54]. Achieving the efficient delivery, high specificity, and non-immunogenicity represent the most crucial challenges standing before epigenome editing [55].…”
Section: Crispr-based Epigenome Editors (Crispr Epi-editors)mentioning
confidence: 99%
“…Interestingly, it has been shown that the composition of extracellular vesicles can be modified by engineering either the producing cells or the vesicles after isolation. Although EVs are considered poorly immunogenic carriers (Saleh et al, 2019), they play a role in mediating immunostimulating or immunosuppressive responses (Robbins and Morelli, 2014).…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%